Peran Guru Dalam Meningkatkan Moral Anak Usia Dini Di Tk It Qurrota A’yun Ponorogo - Hurmaini, Sofi (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2020)
Abstract: This study aims to understand: 1) What is the role of the teacher as a guide in improving the morale of young children in kindergarten IT Qurrota A'yun Ponorogo; and 2) What is the role of the teacher as an educator in improving the morale of young children in kindergarten IT Qurrota A 'Yun Ponorogo. The research used is qualitative research. This type of research is a case study. Data collection techniques in this study used interviews, and documentation. The data analysis techniques taken by the concept proposed by Miles and Huberman are data reduction, data presentation, and discussed conclusions. The results showed that: 1). In accordance with the preconventional morality of children who do not comply with the rules, they are subject to punishment, such as children who argue without reason, the way the teacher reminds them is by singing; 2). Children are born in good condition, so that learning is requested to be processed by being carried out, carried out, and evaluated and then poured into RPPH.